2021
DOI: 10.3389/fmed.2021.630209
|View full text |Cite
|
Sign up to set email alerts
|

An Open Label Trial to Assess Safety of Losartan for Treating Worsening Respiratory Illness in COVID-19

Abstract: Rationale: Coronavirus disease 2019 (COVID-19) can cause disruption of the renin-angiotensin system in the lungs, possibly contributing to pulmonary capillary leakage. Thus, angiotensin receptor blockers (ARBs) may improve respiratory failure.Objective: Assess safety of losartan for use in respiratory failure related to COVID-19 (NCT04335123).Methods: Single arm, open label trial of losartan in those hospitalized with respiratory failure related to COVID-19. Oral losartan (25 mg daily for 3 days, then 50 mg) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…The study found that Losartan was safe for acute respiratory compromise caused by COVID-19. However, randomized trials are required to evaluate true efficacy [ 68 ].…”
Section: Emerging Therapies For Covid-19-induced Ardsmentioning
confidence: 99%
“…The study found that Losartan was safe for acute respiratory compromise caused by COVID-19. However, randomized trials are required to evaluate true efficacy [ 68 ].…”
Section: Emerging Therapies For Covid-19-induced Ardsmentioning
confidence: 99%
“…The first, from University of Kansas, was a single-arm open-label trial assessing the ARB losartan in hospitalized COVID-19 patients requiring oxygen [13]. Thirty active treatment patients vs. 30 post-hoc external controls using propensity scores were compared, with the primary outcome being AE incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the RAS system induces strong oxidative stresses that form the major pathogenic mechanism in COVID19 [ 120 ]. Losartan, being an angiotensin receptor 1 (AT1R) blocker in the RAS pathway, may be useful for COVID-19 patients who experience pneumonia [ 121 , 122 ]. Losartan appears to stimulate ACE2 overexpression and may increase viral entry.…”
Section: Potential Therapeutics For Management Of Covid-19mentioning
confidence: 99%